The Effectiveness of Using Learning Management System (LMS) in Blended Learning Model in The Learning System of 4.0 Era - Hamela Sari Sitompul; Idawati Situmorang; Salim Efendi (Institute of Computer Science (IOCS), 2022)
Technology is one of the suggestions in developing students' potential in finding learning resources outside the classroom. Therefore, Blended Learning combines the two things. In facing the era of the industrial revolution 4.0, a learning system is needed that can form creative, innovative, and competitive students. One of these things can be achieved by optimizing technology as an educational tool. This study aims to apply technological advances in education through the Blended Learning model using LMS and increase student activity in learning. This research method uses classroom action research (PTK) which consists of two cycles and each cycle includes planning, implementation, observation, and reflection. The instrument used is a test of learning outcomes and student activity observation sheets. The results of data analysis from student learning outcomes showed an increase in learning outcomes in each cycle. It is shown by the average value of N-gain in the first cycle of 54.86% while the second cycle is 70.22%. In the assessment of the results of observing student activities during learning in cycle I and cycle II, it showed an increase in an activity wherein cycle I students was very active 8% and in cycle II it became 48%. The results of this study can effectively improve learning outcomes and increase student learning activities.